Treatment method for removal of PN (P-type semiconductor and N-type P-type semiconductor) junction on abnormal silicon chip before single crystal semi-finished product printing - LU XIAOYA; DOU XIAOBO; ZHAN SHIFEI; YANG HUAIJIN (2012)
The invention discloses a treatment method for removal of a PN (P-type Semiconductor and N-type P-type Semiconductor) junction on an abnormal silicon chip before single crystal semi-finished product printing, which comprises the following steps of: removing a silicon nitride film on the silicon chip by using hydrofluoric acid aqueous solution with a volume percentage of 8-10 percent; and removing the P/N junction on the abnormal silicon chip by using sodium hydroxide, alcohol and floss-making additive and carrying out secondary floss-making. The treatment method has the beneficial effect that the silicon nitride film and the P/N junction on the abnormal silicon chip can be effectively removed.